A Psycho‐Educational Intervention for People with a Family History of Depression: Pilot Results. Issue 2 (29th September 2016) - Meiser, Bettina; Peate, Michelle; Levitan, Charlene; Mitchell, Philip B; Trevena, Lyndal; Barlow‐Stewart, Kristine; Dobbins, Timothy; Christensen, Helen; Sherman, Kerry A; Dunlop, Kate; Schofield, Peter R
Abstract: We developed and pilot‐tested the first online psycho‐educational intervention that specifically targets people with a family history of depression (' LINKS' ). LINKS provides genetic risk information and evidence‐rated information on preventive strategies for depression and incorporates a risk assessment tool and several videos using professional actors. LINKS was pilot‐tested in the general practitioner (GP) setting. The patient sample included people with a family history of at least one first‐degree relative (FDR) with major depressive disorder (MDD) or bipolar disorder (BD). Patients attending participating GP practices were invited to enroll in the study by letter from their GP. Patients who self‐identified as having at least one first‐degree relative (FDR) with MDD or BD were eligible. Patients completed questionnaires, pre‐post viewing LINKS, with measures assessing satisfaction, relevance, emotional impact and perceived improvement of understanding. Six GP practices participated, and 24 patients completed both questionnaires. Of these, all reported that they were satisfied or very satisfied with LINKS, and 74 % reported that LINKS met their expectations, and 21 % that it exceeded their expectations. LINKS was judged highly acceptable by this sample of GP attendees, and results indicate that an assessment of its effectiveness in a larger controlled trial is warranted.